Javanese-Islamic Syncretism in Islamic Legal Ethnography: Religious and Cultural Fluidity in Sesajian Traditions - Hudzaifah, Ayu; Hutami, Nestiani (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
As Muslims, local culture cannot be separated from the Islamic religion, which is adhered to by the majority of the Indonesian population, particularly on the island of Java. For Muslims on Java Island, not all local culture is under the teachings of the Islamic religion, which originates from the Holy Qur’an and Hadith. One of the local cultures strong in Javanese nuances is the cultural practice of offerings. Although offerings are considered heresy and idolatry in Islam, they are still carried out by residents of Rembu Lor village, Mojokerto Regency, East Java, which has the distinctive name “Cok Bakal”. In this research, the researchers focus on the form of syncretization existing in the “Cok Bakal” and Islam’s perspective on this cultural practice. The researchers employed an ethnographic approach, which began with participant observations, documentation, and interviews during ten months of field research. The research results show that during the “Cok Bakal” procession, the community also conducted Islamic teachings, such as istighosah, sholawat, and hajat prayers. In Islam, the practice of offerings is considered shirk. However, since the offerings practice of “Cok Bakal” has been passed down from generation to generation, a constructive dialogue and ongoing education may encourage the community to understand Islamic teachings better. In conclusion, in addressing the culture of offerings, it is essential to consider broader social and cultural aspects while still adhering to Islamic principles.